Rapid Electrochemical-Based PCR-Less Microbial Quantification and Antimicrobial Susceptibility Profiling Directly From Blood and Urine With Unknown Microbial Load or Species - Chen, Jade; Navarro, Eduardo; Nuñez, Eliseo; Gau, Vincent (Frontiers in Bioengineering and Biotechnology, 2021)
Novel molecular platforms are available for identifying (ID) the causative agents of microbial infections and generating antimicrobial susceptibility testing (AST) profiles, which can inform the suitable course of treatment. Many methods claim to perform AST in minutes or hours, often ignoring the need for time-consuming steps such as enrichment cultures and isolation of pure cultures. In clinical microbiology laboratories, an infectious microbial must first be cultured (overnight to days) and identified at the species level, followed by a subsequent AST with an additional turnaround time of 12 to 48 hours due to the need for regrowth of the organism in the absence and presence of relevant antibiotics. Here, we present an electrochemical-based direct-from-specimen ID/AST method for reporting directly from unprocessed urine and blood in hours. In a limit of detection study of 0.5-mL whole blood samples for point-of-care and pediatric applications, only 16.7% (4/24) of samples contrived at 2 CFU/mL were reported positive and 100% (24/24) of samples contrived at 6 CFU/mL were tested reported positive in 6.5 hours, indicating a limit of detection of 6 CFU/mL. In a separate direct-from-specimen AST study, the categorical susceptibility was reported correctly for blinded susceptible, intermediate, resistant, and polymicrobial contrived specimens in 4 hours.